Assembly of Liquid-based thermoelectric generator modules based on amine bonding. (2021) - Jeandupeux, Laure; Laux, Edith; Prieur, Claudio; Potty, Philippe; Keppner, Herbert
Abstract: In the previous years, it has been shown that ionic liquids (IL) are good candidates as base material for thermo-electric generators (TEG). Having identified promising ILs, the next step is building a module integrating those liquids and enabling its use with consumer devices. To keep the flexibility given by a liquid TEG, all the involved materials must be flexible. A TEG is composed of three different layers: 1) the bottom electrode foil, 2) a core foil, containing cavities with liquids, and 3) the top electrode foil. The core foil must be flexible, tight, easily shaped and must exhibit a low thermal conductivity. Inspired by microfluidics, polydimethylsiloxane (PDMS) was chosen. The electrode foils have to withstand metal coating and patterning, must be flexible while retaining electrical conductivity, and must not react with the liquids. Unfortunately, PDMS is not easily bonded to another polymer. Moreover, hermetic sealing of the liquids in a cavity while keeping the contact with the electrode is critical. The TEG being serial connected, if one junction fails the entire TEG fails. In this paper, we demonstrate a way to create the module first by using amine-based bonding of the liquids-accepting housing, and then filling the core cavities with liquids featuring different Seebeck coefficients, using a home built vacuum chamber. The results on bonding and filling are encouraging; they ensure tightness of all the 100 TEG contacts between ILs and electrodes. A Seebeck coefficient (SE) of 1 mV∙K −1 was measured, which is inferior to the expected value and thus asking for multiple improvements. However, the results must rather be seen as a proof of concept, especially concerning the sealing of the liquid, and as a step in the manufacturing process of highly integrated liquid-containing devices.